Pelatihan Diversifikasi dan Digitalisasi Usaha Tanaman Hias Berbasis Ekonomi Kreatif Untuk Mewujudkan Kemandirian Ekonomi Perempuan Kampung Bunga Madirsan Desa Bangun Sari, Kec. Tanjung Morawa, Kab. Deli Serdang, Sumatera Utara - Novi Handayani Simbolon; Fatma Dwi Jati; Sondang Beatrix Siahaan; Muhammad Asrin Jazuli; Khanti Listya (Politeknik Piksi Ganesha Indonesia, 2026)
Abstract: Kampung Bunga Madirsan is known as a center for ornamental plant sales, serving as a primary source of income for women in the area. However, in recent times, ornamental plant sales have seen a significant decline. This is due to a lack of variety in ornamental plant products, a lack of innovation in packaging, and limited ability to utilize digital media as a marketing tool. Partners also lack branding strategies and marketplace sales strategies, relying solely on conventional methods. Partners also rely on the use of chemical fertilizers, increasing their costs. This situation has resulted in limited market reach and low growth in ornamental plant businesses. This community service activity aims to address these partner challenges through training on diversification and digitalization of ornamental plant businesses based on the creative economy. The implementation method includes an initial survey, participatory training, provision of technological tools to facilitate plant care, hands-on practice, mentoring, and the creation of digital business profiles for partners in Kampung Bunga Madirsan